Rule of Law and National Autonomy in the European Union: Who Defines the Boundaries? - Godál, Karolína (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2025)
This article examines the evolving tension between national autonomy and the European Union’s common concept of the rule of law, with a particular focus on judicial independence. While Article 2 TEU frames the rule of law as a value common to all Member States, recent jurisprudence— especially involving Poland—has exposed significant divergences between national and EU-level interpretations. The independence of the judiciary has become a key issue, raising questions about the autonomy Member States have when changing their justice systems and the limits of EU intervention. The article analyses how the EU defines and enforces the rule of law and whether a genuinely “common” understanding exists. In this context, the Polish case illustrates the legal and institutional difficulties involved in restoring the rule of law, highlighting the complex interplay between EU legal obligations and national constitutional identity.